2007
DOI: 10.1152/ajprenal.00316.2007
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of upstream stimulatory factor 2 accelerates diabetic kidney injury

Abstract: Liu S, Shi L, Wang S. Overexpression of upstream stimulatory factor 2 accelerates diabetic kidney injury. Am J Physiol Renal Physiol 293: F1727-F1735, 2007. First published September 19, 2007; doi:10.1152/ajprenal.00316.2007.-Diabetic nephropathy is the most common cause of end-stage renal failure in the United States. Hyperglycemia is an important factor in the pathogenesis of diabetic nephropathy. Hyperglycemia upregulates the expression of transforming growth factor-␤ (TGF-␤), which stimulates extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
0
27
0
2
Order By: Relevance
“…34,35 Moreover, streptozotocin-treated TSP1 null mice do not develop glomerulosclerosis or podocyte loss, 36 and mice with induced expression of USF2 have increased TSP1 expression, TGF-␤ activity, and renal fibrosis. 37 TSP1 expression correlates with proteinuria in patients with type 2 diabetes, 34 and glycated albumin stimulates increased TSP1 expression and tubular hypertrophy. 38 Moreover, antagonism of TSP1-dependent TGF-␤ activation by treatment with a peptide antagonist of TSP1-dependent TGF-␤ activation, LSKL, reversed myocardial fibrosis and improved left ventricular function by reducing TGF-␤ activity in diabetic rats.…”
mentioning
confidence: 92%
“…34,35 Moreover, streptozotocin-treated TSP1 null mice do not develop glomerulosclerosis or podocyte loss, 36 and mice with induced expression of USF2 have increased TSP1 expression, TGF-␤ activity, and renal fibrosis. 37 TSP1 expression correlates with proteinuria in patients with type 2 diabetes, 34 and glycated albumin stimulates increased TSP1 expression and tubular hypertrophy. 38 Moreover, antagonism of TSP1-dependent TGF-␤ activation by treatment with a peptide antagonist of TSP1-dependent TGF-␤ activation, LSKL, reversed myocardial fibrosis and improved left ventricular function by reducing TGF-␤ activity in diabetic rats.…”
mentioning
confidence: 92%
“…We previously demonstrated that USF2 was upregulated in the kidney from diabetic animals as well as in the mesangial cells after acute high-glucose exposure and plays an important role in the development of diabetic nephropathy through regulation of TSP1 and TSP1-dependent TGF-␤ activity (23,30,35). Our current studies revealed a new regulatory mechanism of USF2 expression in mesangial cells under diabetic conditions, e.g., glycated albumin-mediated upregulation of USF2.…”
Section: Discussionmentioning
confidence: 49%
“…We demonstrated that USF2 binds to an 18-bp sequence in the thrombospondin1 (TSP1) gene promoter and regulates high glucose-induced TSP1 expression and TSP1-dependent TGF-␤ activity in mesangial cells (35). Moreover, overexpression of USF2 stimulates TSP1 expression, TGF-␤ activity, and extracellular matrix protein expression in the kidney and accelerates the development of diabetic nephropathy (23). All these studies suggest that USF2 is an important regulator of diabetic nephropathy.…”
Section: Nf-bmentioning
confidence: 94%
“…A expressão de USF2 já havia sido demonstrada em células mesangiais [111][112][113][114][115] , e aparenta estar diretamente relacionada com o desenvolvimento de doenças renais crônicas, incluindo a nefropatia diabética. Sua expressão encontra-se aumentada sob condições de altas concentrações de glicose; além disso, trabalhos indicam que a atividade de TGFβ é estimulada pelo fator USF2 [112][113][114][115] .…”
Section: Tgfβ-1 E Usf2 Estimulam a Expressão Do Gene Pró-apoptótico Bunclassified
“…Sua expressão encontra-se aumentada sob condições de altas concentrações de glicose; além disso, trabalhos indicam que a atividade de TGFβ é estimulada pelo fator USF2 [112][113][114][115] .…”
Section: Tgfβ-1 E Usf2 Estimulam a Expressão Do Gene Pró-apoptótico Bunclassified